The Role of Cognitive Behavior Therapy in Intervention Management to Overcome Social Pathology in Commercial Sex Workers - Ramadan, Muhammad Jumadi; Fatmah, Nor (Lembaga Yasin AlSys, 2026)
This study analyzes the role of Cognitive Behavioral Therapy (CBT) in intervention management for female commercial sex workers (CSWs), with emphasis on cognitive mechanisms, behavioral change processes, and integration with socioeconomic support. The study focused on AR, a 30-year-old CSW in Palangka Raya who participated in CBT-based counseling involving cognitive restructuring, behavioral experiments, emotion-regulation training, and basic vocational-skills tasks. Data were collected through semi-structured interviews, participant and non-participant observation, and counseling documentation, then analyzed thematically using data triangulation and reflexivity to strengthen credibility. The findings indicate that addressing core maladaptive beliefs reduced shame, hopelessness, and nihilistic schemas, while behavioral tasks, including job interview simulations, resume building, and graded social exposure, provided experiential evidence of alternative livelihoods and increased self-efficacy. Emotion-management techniques also improved impulse control and reduced reactive decision-making associated with economic stress. However, dysfunctional family contexts, stigma, and economic pressures limited the sustainability of intervention outcomes. The results further show that CBT outcomes improved when combined with family psychoeducation, social support linkages, and referrals to vocational and economic-assistance services. The study concludes that modular CBT integrating cognitive restructuring, behavioral activation, life-skills development, and socioeconomic support offers a promising intervention model for CSW populations, although the single-case design limits generalizability and causal inference. This study contributes to counseling and social intervention literature by providing process-based insights into how CBT may support psychological, behavioral, and socioeconomic change among vulnerable women, while highlighting the need for larger, controlled, culturally adapted studies with long-term monitoring.